Spectrophotometric determination of Phenylephrine hydrochloride and Salbutamol sulphate drugs in pharmaceutical preparations using diazotized Metoclopramide hydrochloride - Baghdad Science Journal (مجلة بغداد للعلوم, 2015)
A spectrophotometric method has been proposed for the determination of two drugs containing phenol group [phenylephrine hydrochloride (PHP) and salbutamol sulphate (SLB)] in pharmaceutical dosage forms. The method is based on the diazotization reaction of metoclopramide hydrochloride (MCP) and coupling of the diazotized reagent with drugs in alkaline medium to give intense orange colored product (?max at 470 nm for each of PHP and SLB). Variable parameters such as temperature, reaction time and concentration of the reactants have been analyzed and optimized. Under the proposed optimum condition, Beer’s law was obeyed in the concentration range of 1-32 and 1-14 ?g mL-1 for PHP and SLB, respectively. The limit of detection (LOD) and limit of quantification (LOQ) for each of PHP and SLB were 0.60, 0.52 ?g mL-1 and 2.02, 1.72 ?g mL-1, respectively. No interference was observed from common excipients present in pharmaceutical preparations. The good correlation coefficients and low relative standard deviation assert the applicability of this method. The suggested method was further applied for the determinations of drugs in commercial pharmaceutical preparations, which was compared statistically with reference methods by means of t- test and F- test and were found not to differ significantly at 95% confidence level. The procedure was characterized by its simplicity with accuracy and precision.